2022
DOI: 10.9734/ejmp/2022/v33i630469
|View full text |Cite
|
Sign up to set email alerts
|

The Comparative Effects of Vitamin E + C on the Chronic Toxicity of Paraquat in Albino Rats (Rattus norvegicus)

Abstract: Paraquat is a highly toxic chemical used in weed control. Paraquat is known for its ability to generate reactive oxygen species that attack cells and membranes. Vitamin E is a group of vitamins which dissolves in fat and possess antioxidant properties which act as a defense to the cells against oxidative stress arising from reactive oxygen species, whereas Vitamin C is a water soluble vitamin and a very potent antioxidant which protects the cells of the body from free radicals. The study aim was to evaluate th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 0 publications
1
11
0
Order By: Relevance
“…The significant change in urea level may not necessary depict optimal kidney health because study conducted by same author and other colleagues revealed that paraquat intoxication resulted in significant decrease in total protein levels. Since urea is the by-product of protein metabolism, urea may not rise because protein levels are usually low in paraquat intoxication (Okolonkwo et al, 2022a;Okolonkwo et al, 2022b).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The significant change in urea level may not necessary depict optimal kidney health because study conducted by same author and other colleagues revealed that paraquat intoxication resulted in significant decrease in total protein levels. Since urea is the by-product of protein metabolism, urea may not rise because protein levels are usually low in paraquat intoxication (Okolonkwo et al, 2022a;Okolonkwo et al, 2022b).…”
Section: Discussionmentioning
confidence: 99%
“…After the duration of the treatment period, the rats were sedated using chlorofoam, sacrificed and blood sample was collected my means of cardiac puncture (Okolonkwo et al, 2022b).…”
Section: Experimental Designmentioning
confidence: 99%
“…After that, we positioned the slanted needle inside the rat's mouth horizontally, making sure to avoid the teeth in the middle. Paraquat was slowly dispensed from the syringe into the rat's mouth [10].…”
Section: Methods For Paraquat Treatmentmentioning
confidence: 99%
“…Manually determining ALP requires the following formula: IU/L = 2760 x A 405 nm/min. Gamma-Glutamyltransferase (GGT) method: by Okolonkwo et al (2022) [10].…”
Section: Manual Calculationmentioning
confidence: 99%
“…Each group mentioned was subdivided into two subgroups designed "0" and "VEC" so that the total number of subgroups were 8; A0 and AVEC, B0 and BVEC, C0 and CVEC, and D0 and DVEC. All "VEC" subgroups (AVEC, BVEC, CVEC and DVEC) were treated with 500mg of vitamin E and 2000mg/dl of vitamin C every week for 3 months [10].…”
Section: Methodsmentioning
confidence: 99%